Experimental sociology outline of a scientific field - Barrera, Davide 1968-; Gërxhani, Klarita 1973-; Kittel, Bernhard 1967-; Miller, Luis; Wolbring, Tobias 1982- (Cambridge University Press, 2025)
"Expertly navigates students and scholars through pivotal concepts of the experimental approach necessary for addressing sociological research questions. It furnishes readers with a profound understanding of sociological experiments, empowering them to seamlessly translate theoretical reasoning into skillfully designing experiments with confidence"--
Includes bibliographical references and index
Keywords: Sociology / Experiments; Sociology / Methodology; Experimental design; Social sciences / Experiments